Edukasi Pemberian Gizi Seimbang dalam Gerakan ‘Aisyiyah Cinta Anak untuk Pencegahan Stunting pada Remaja Panti Asuhan ‘Aisyiyah di Kubu Raya - Melly Nirma Syahriani; Ayuk Novalina (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Adolescence is the the physical growth and development, mental, and the activity of causing the increasing demand zat-zat nutritional intake.The more a problem still happens and national nutrition is stunting.Stunting in toddlers characterized by body size of being short of kognitf ability was accompanied by low.Based on a survey the nutritional status under five year 2022, the prevalence of stunting 21,7 % in indonesia is about, who have not met the target % is as much as 20.The provision of knowledge and education can influence as part of efforts to prevent stunting.The purpose of the nutrition education implemented in a balanced aisyiyah filial aisyiyah orphanage in adolescents in kubu raya teenagers to increase knowledge about nutrition balanced for the prevention of juvenile stunting. Method of implementation by doing pre-post health counseling tests on balanced nutrition for the prevention of stunting on adolescents.The target of this activity is a teenage foster home in the pontyya area of the country..The results based on pre and post-test data obtained are known to be an increase in teenage knowledge of nutrition balanced for stunting prevention in teenagers, which is 59 responders had 19 responders who had less knowledge of 32.20 % before being given a good knowledge of 33 people or 55.9 % after being given counseling rawing conclusions the devotion to the community in the form of information about nutrition balanced for the prevention of stunting to teenagers can increase knowledge teenagers and it is very important to prepare teenagers productiveAdolescents